PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X TEKNIK SEPEDA MOTOR SMK NEGERI 1 SIMPANG KANAN - Puput Wiyanto; Zuhri D '; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: The research was classroom action research that aims to improve learning process and mathematics learning outcomes with applied the cooperative learning Think Pair Square (TPS) structural approach. The subject of the research is students of class X Motorcycle Engineering SMK Negeri 1 Simpang Kanan in the second semester academic years 2015/2016. There are 28 students in the class, consist of 20 boys who have heterogeneous academic ability. The research are two cycles. Each a cycle has four stages, that are planning, implementation, observation, and reflection. Each end of the cycle of daily tests carried out. The instrument of data collection on this research are observation sheets and mathematics learning outcomes tests. Analysis data of observation was performed with narrative descriptive analysis and analysis data of mathematics learning outcomes was performed with descriptive statistical analysis. From the narrative descriptive analysis showed an improvement of learning process from the prior action to the first cycle and the second cycle. The results of this research showed an increasing number of students learning Mathematic from the basic score are 8 students with percentage 28.57 % to 10 students with percentage 35.7 % on the first test and 13 students with percentage 46.4 % on second test. Results of this research indicates that applied the cooperative learning cooperative learning think pair square structural approach can improve learning process and students' mathematics learning outcomes math class X Motorcycle Engineering SMK Negeri 1 Simpang Kanan in the second semester academic years 2015/2016.Key words: Mathematics learning outcome, Cooperative learning, Pair Check.